2018
DOI: 10.1111/cen.13851
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abnormal semen analysis and levels of adherence with fertility preservation in men undergoing therapy for newly diagnosed cancer: A retrospective study in 2906 patients

Abstract: This study expands understanding of the semen quality of men with newly diagnosed cancer, and their ability to adhere to fertility preservation recommendations. Our data suggest that patients with the poorest semen quality paradoxically suffer the poorest attendance rates of sperm cryopreservation appointments prior to commencing cancer therapy. We suggest that additional support may be of clinical benefit to men with newly diagnosed cancer and TMC < 1 million sperm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We concluded that the urgent treatment time for further treatment might be the reason for this result. A study showed that sperm total motile count (TMC) < 1 million was the second most prevalent category of sperm quality among leukaemia patients during the first visit for semen collection [ 22 ]. It is imperative to communicate with clinicians in a timely manner to ensure that leukaemia patients bank sperms before cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that the urgent treatment time for further treatment might be the reason for this result. A study showed that sperm total motile count (TMC) < 1 million was the second most prevalent category of sperm quality among leukaemia patients during the first visit for semen collection [ 22 ]. It is imperative to communicate with clinicians in a timely manner to ensure that leukaemia patients bank sperms before cancer treatment.…”
Section: Discussionmentioning
confidence: 99%